The internal migration of the Saudi population in the Kingdom of Saudi Arabia, according to the 2004 census - حسين الزيادي (آداب الكوفة, 2011)
Internal migration is one of the important aspects of population movement within the region, and it is difficult to measure it at the national level unless the population censuses include data on immigrants, their places of origin, and the dates of their arrival to the enumeration areas. Within the city itself, there is no doubt that internal migration has an important impact on population structures and distribution, as well as its importance in terms of population growth within the administrative borders of the state.